PROFESSIONAL TRAINING OF PHYSICAL EDUCATION SPECIALISTS: THE HISTORICAL ASPECT (end of the 19th - the beginning of the 20th century) - Dereka, Tetiana (The Modern Higher Education Review, 2018)
The article describes the peculiarities of physical education specialists’professional training in the period from the end of the XIX to the beginning of the XX century. The professional activity of P. Lesgaft, O. Butovsky, I. Boersky, O. Anokhin as the founders of the national physical education was investigated. The methods of Lesgaft, Butovsky, Bobersky, Anokhin, aimedtoa person’sharmonious development and findingthe solution of physical education specialists’ professional training problem, while each of them set specific tasks and offered their own means of solving them, were characterized. The professional training of physical education specialists is described in the historical aspect. The characteristic features of national physical education and sport specialists’ professional training systemformation and development period in Ukraine in the twentieth century are defined. The first specialized physical education and sports pedagogical institutes of the beginning of the 20-th century are mentioned.